High-Sensitivity C-Reactive Protein Is an Independent Risk Factor for Non-Vertebral Fractures in Women and Men: the Tromsø Study - Dahl, Kristoffer Jensen (UiT Norges arktiske universitet, 2014)
We tested the hypothesis that high-sensitivity C-reactive protein (CRP) is an independent risk factor for non-vertebral fractures, and that CRP is associated with BMD, in both genders. We included 1902 women and 1648 men aged 55 and 74 years, who had CRP measured at baseline in the Tromsø Study, Norway in 2001. All non-vertebral fractures were registered from X-ray archives during an average of 7.2 years follow-up. Cox’s proportional hazard models were used for fracture prediction by CRP and linear regression analyses for its association with BMD, and adjusted for other risk factors. Each SD increase in log CRP increased the risk for non-vertebral fracture by 13% in women and 22% in men. Those with CRP in the upper tertile, exhibited a 39% and 80% higher risk for fracture than those in the lowest tertile in women and men, respectively. Higher levels of CRP were associated with lower BMD in men, not in women. CRP is an independent risk factor for non-vertebral fractures in both genders. As the association between CRP and BMD showed conflicting results, we infer that inflammation may influence fracture risk differently in women than men via factors beyond what is explained by the association between CRP and BMD.